Prevalence and Pattern of Cardiovascular Diseases among ESRD Patients Undergoing Short Term and Long Term Hemodialysis - Shrestha, Manoj; Aryal, Prakash (Journal of College of Medical Sciences-Nepal, 2020)
Background: Cardiovascular diseases (CVD) are the major causes of mortality and morbidity among End Stage Renal Disease (ESRD) patient undergoing hemodialysis (HD). The cardiovascular diseases in dialysis patient is related to chronic volume overload, anemia, inflammation, oxidant stress, homocysteine and other aspects of the uremic milieu. The duration of ESRD undergoing dialysis is related to the severity of cardiovascular diseases. The objective is to study the pattern of cardiovascular disease among the ESRD patient undergoing dialysis. Methods: This comparative study was done at Collage of Medical Sciences Bharatpur, Nepal from 1st June 2020 to 30th July 2020. This study included total number of 300 dialysis patients divided into two groups; 150 patients undergoing dialysis for less than one year and rest undergoing dialysis for more than one year. Patients with primary heart disease were excluded from study. Patients were evaluated with demographic data, clinical history, and physical examination with focus on cardiovascular system, lab investigations, electrocardiography (ECG) and echocardiogram variables. The pattern of cardiovascular diseases was compared among patients undergoing short term and long term hemodialysis. Results: The echocardiographic evaluation of the cases under study revealed a diversity of pattern. In this study concentric or eccentric LVH was found in 60 %( n=90) of patients with short-term hemodialysis and 75 %( n=112) of patients with long-term hemodialysis. 30 %( n=45) of patients with short-term hemodialysis had degenerative/atherosclerotic valvular heart disease while the number was 35%(n=52) in patients undergoing long-term hemodialysis. Pericardial effusion was present in 9 %( n=13) of short-term hemodialysis patient and in 5%(n=7) of long-term hemodialysis patient. 18%(n=27) of short-term hemodialysis patient had systolic dysfunction while such change was present in 27%(n=40) of long-term hemodialysis patient. Diastolic dysfunction was present in 35%(n=52) of short-term hemodialysis patient and 49%(n=73) of long-term hemodialysis patient. Pulmonary Artery Hypertension(PAH) was present in 20%(n=30) of short term hemodialysis patient and 32%(n=48) of long term hemodialysis patient. Atrial fibrillation was present in 7 %(n=10) of short-term hemodialysis patient and 5%(n=7) of long term hemodialysis patients. Conclusions: Variety of cardiovascular diseases are common in ESRD patient undergoing hemodialysis. CVD is more prevalent in patient undergoing hemodialysis for long term.